A prospective study on the impact and out-of-pocket costs of dengue illness in international travelers - Tozan, Yeşim; Wilder-Smith, Annelies (The American journal of tropical medicine and hygiene, 2019)
Abstract. Although the costs of dengue illness to patients and households have been extensively studied in endemic populations, international travelers have not been the focus of costing studies. As globalization and human travel activities intensify, travelers are increasingly at risk for emerging and reemerging infectious diseases, such as dengue. This exploratory study aims to investigate the impact and out-of-pocket costs of dengue illness among travelers. We conducted a prospective study in adult travelers with laboratory-confirmed dengue and recruited patients at travel medicine clinics in eight different countries from December 2013 to December 2015. Using a structured questionnaire, we collected information on patients and their health-care utilization and out-of-pocket expenditures, as well as income and other financial losses they incurred because of dengue illness. A total of 90 patients participated in the study, most of whom traveled for tourism (74%) and visited countries in Asia (82%). Although 22% reported hospitalization and 32% receiving ambulatory care while traveling, these percentages were higher at 39% and 71%, respectively, after returning home. The out-of-pocket direct and indirect costs of dengue illness were US$421 (SD 744) and US$571 (SD 1,913) per episode, respectively, averaging to a total out-of-pocket cost of US$992 (SD 2,052) per episode. The study findings suggest that international travelers incur important direct and indirect costs because of dengue-related illness. This study is the first to date to investigate the impact and out-of-pocket costs of travel-related dengue illness from the patient’s perspective and paves the way for future economic burden studies in this population.
Gesehen am 12.09.2019